Globalization and progressive economic policy - Baker, Dean 1958-; Epstein, Gerald A. 1951-; Pollin, Robert 1950- (Cambridge University Press, 1998)
The authors of this book challenge mainstream thinking about the nature of globalization. While not hostile to markets per se, they believe that capitalist market processes, left to operate freely, tend to generate injustice, insecurity, instability, and inefficiency. Taking account of the new realities of globalization, this volume explores an unusually wide range of subjects, including trade integration, multinational corporations, labor markets and migration, international capital flows, macroeconomic and environmental policy, and the central roles of the IMF and World Bank. It proposes alternatives to neo-liberal orthodoxy, developing policy measures that counter the destructive features of markets and promote equality as well as efficiency. The approach in this volume is particularly illuminating for understanding the Asian financial collapse of 1997–98 and similar recent crises. The volume also includes comments on each chapter by a wide range of distinguished economists, producing a lively and often controversial set of interchanges